Implementation of Social-Studies Teaching Materials Based on Flipbook for Student Learning of Po'o Elementary School - Fatima, Siti; Hasan, Hasan; Jamaludin, Jamaludin (Journal of Education Method and Learning Strategy, 2025)
Education is factor main in progress a country, because through education , the state can print source Power quality human beings . This is in accordance with quote that says that " education is one of business For develop potential students , through planned business​ so that student to obtain intelligence in aspect knowledge , skills as well as positive attitude ” . Formulation problem study how is the application process flipbook -based social studies teaching materials for students class IV SDN Po'o , how impact implementation flipbook -based social studies teaching materials for activity Study student class IV SDN Po'o . Research objectives For describe the implementation process flipbook -based social studies teaching materials for students Class IV of Po'o Elementary School , For describe impact implementation social studies teaching materials based on flipbook vs. activity Study student Class IV SDN Po'o . Research methods qualitative is collecting data in the form of words or images , so that No emphasizes on numbers . Research Results From the beginning activity learning implementation flipbook- based social studies teaching materials , the teacher explains how to do it use the teaching materials . This is seen in the results observation on aspects teacher readiness that has fulfil indicator said . Research Conclusion Implementation flipbook -based social studies teaching materials for students Grade IV of Po'o State Elementary School proven effective in activity learning . This is seen from results observations obtained​ that implementation Flipbook -based social studies teaching materials are in the category well , with mark presentation is 87.5%.